Efetividade de uma intervenção educativa para pacientes sobre segurança do paciente no autocuidado e na autoeficácia: estudo quase experimental - Perego, Maira Gabriela (Universidade Federal de São Carlos, 2022)
Introduction: Patient safety is a global health problem and the patient, in this context, becomes an active member, more aware and empowered of their rights and responsibilities as a consumer of health services, contributing to the improvement of quality, safety assistance provided and success in their treatment. Objective: To analyze the effectiveness of an educational intervention on patient safety in the self-care and self-efficacy of hospitalized patients. Methods: Quasi-experimental research (ReBEC registration nº RBR-8gzp4f4) with a non-equivalent control design, comprising 2 steps: 1) Scope review, in the WOS, PubMed, CINAHL and LILACS databases, without period limitations, with the objective of supporting the construction and validation of educational material on patient safety by following specific guidelines for the elaboration of educational health materials and consulting 5 experts in the area of interest; 2) Educational intervention on patient safety, carried out at the HU-UFSCar and Santa Casa de Araraquara, with patients hospitalized in the medical and surgical clinic wards. Participants were divided into two groups: CG (control group), which received usual care from hospital institutions and GI (intervention group), which participated in an educational intervention on patient safety; the collection occurred first in the CG and after the end, in the IG. The variables analyzed were self-care and self-efficacy, in two moments: first – up to 96 hours after hospital admission and the second – from 24 to 96 hours after usual care or educational intervention. Both outcome variables underwent a normality test. For qualitative variables, the chi-square test was used; the Mann Whitney test was applied for those with two classes and the Kruskall Wallis test with post Bonferroni test for the variables with more than two classes. In the evaluation of the CG and IG before and after the educational intervention, the Generalized Linear Models were used. Results: In the first stage of the study, scope review, 3237 articles were found, of which 53 met the inclusion criteria and constituted the final sample; the articles were analyzed and categorized according to the information relevant to the patients regarding: 1) Fall Prevention; 2) Correct Identification of the Patient; 3) Medication Safety and; 4) Hand Hygiene. Based on the results of the scoping review and on the assumptions of health literacy, the educational booklet “Patient Safety: important information for patients and caregivers about hand hygiene, preventing falls, correct identification and flawless medication” was proposed, which obtained an index content validity of 0.98. In the second stage, a total of 158 health users participated in the study, with 79 in the control group and 79 in the intervention group. It was observed that there is no association between sociodemographic characteristics and the control group and intervention group (p > 0.05) and a statistically significant difference between the variables antecedent of diabetes (p = 0.003) and other health history (p = 0.012). The intervention group obtained higher scores in the levels of self-care and self-efficacy (p=0.001 and p=0.033) than the control group and after the educational intervention and usual care, the levels of self-efficacy showed statistically higher results (p=0.026). Conclusions: In conclusion, the results presented in this thesis showed that the educational intervention in patient safety, with the educational booklet “Patient Safety: important information for patients and caregivers about hand hygiene, preventing falls, correct identification and medication without fail”, is an effective strategy to increase the self-efficacy and self-care of hospitalized patients.
Effectiveness of an educational intervention for patients on patient safety in self-care and self-efficacy: quasi-experimental study
Keywords: Segurança do paciente; Educação em saúde; Educação de pacientes como assunto; Estudos quasi-experimentais; Patient safety; Health education; Patient education as topic; Quasi-experimental studies; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA